Repercussions of the COVID-19 pandemic on the health profile of Physiotherapy students - Vieira, Luciane Correia da Silva; Campos, Amanda Souza; Marques, Daniel da Silva (O Mundo da Saúde, 2023)
The first case of the coronavirus disease (COVID-19) pandemic was located in Wuhan, China, in December 2019. As it is considered infectious and highly contagious, causing respiratory problems, it has led to numerous changes in the academic calendar of educational institutions. The present study aims to track the profile of physiotherapy students, recognizing the impacts of the pandemic on their overall health, as well as examining the greatest academic difficulties during this period. This is a qualitative data survey, collected from Centro Universitário São Camilo (CUSC) students during the months of August, September, and October 2021, totaling 169 responses. It was observed that during the pandemic, 45 (26.6%) students had some health problems. As for daily activities, 111 (65.7%) stated that they managed to adapt leisure activities at home, 84 (49.7%) worsened their eating habits, and 57 (33.7%) stated that they had less than eight hours of sleep. Regarding online learning, 68 (40.2%) considered their academic performance regular and 156 (92.3%) felt impaired in some way. In addition, 111 (65.7%) considered remote learning extremely stressful, where the majority opted for in-person classes, with 77 (45.6%) wanting to resume in-person activities completely, and 76 (45.0%) opted for a gradual return. It was found that the profile of CUSC physiotherapy students underwent significant changes in several aspects, such as sleep and diet, but mainly psychological and academic issues were referred to, with positive and negative points concerning online learning.